2001
DOI: 10.15369/sujms1989.13.247
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory Responses to Scootering in Comparison with Walking, Running and Cycling

Abstract: Physiological responses to riding a scooter (scootering) are compared with walking, running and cycling at three different treadmill speeds (80, 110 and 140m mint) and slopes (0 %, 4 % and 8 %). Five healthy male college students performed all exercises at different intensities in four trials a day, one or two days a week. Each experiment comprised of a 5-20 minute resting period, followed by 3 minutes of exercise and 10-50 minute recovery time. Apart from stationary cycling to measure maximal oxygen uptake, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Comparing the MET values between the scootering in this study and the walking (80 m • min Ϫ1 )/running (140 m • min Ϫ1 ) reported by Ainsworth et al (1993Ainsworth et al ( , 2000, the scootering value is slightly higher, at 80 m • min Ϫ1 and remarkably lower at 140 m • min Ϫ1 . This feature is almost the same as the feature of VO 2 in our previous study (Kijima et al, 2001), where there was no significant difference at 80 m • min Ϫ1 between scootering and walking. There was no statistically significant difference in the VO 2 (ml • kg Ϫ1 • min Ϫ1 ) between the female group and the male group at the three scootering speeds, which agrees with the study of bicycling that Adams (1967) reported.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Comparing the MET values between the scootering in this study and the walking (80 m • min Ϫ1 )/running (140 m • min Ϫ1 ) reported by Ainsworth et al (1993Ainsworth et al ( , 2000, the scootering value is slightly higher, at 80 m • min Ϫ1 and remarkably lower at 140 m • min Ϫ1 . This feature is almost the same as the feature of VO 2 in our previous study (Kijima et al, 2001), where there was no significant difference at 80 m • min Ϫ1 between scootering and walking. There was no statistically significant difference in the VO 2 (ml • kg Ϫ1 • min Ϫ1 ) between the female group and the male group at the three scootering speeds, which agrees with the study of bicycling that Adams (1967) reported.…”
Section: Discussionsupporting
confidence: 85%
“…All scootering was performed on a motor-driven treadmill (Treadmill ® , Nishikawa Iron Works, Tokyo, Japan) on a level surface at three different speeds, 80, 110, and 140 m • min Ϫ1 , which were calibrated whenever necessary. The scooter speeds were set on the supposition that people are likely to move at this range of speed, which does not deviate from the safety range on the treadmill (Kijima et al, 2001;Arimoto et al, 2002). The scooter used in this study (Micro ® , Micro Mobility Systems, Kusnacht, Switzerland) weighs 2.8 kg and consists of two wheels of 100 mm in diameter, a narrow board of 100 mm width and 565 mm length between the wheel centers, and an adjustable 850 mm high steering apparatus.…”
Section: Scooter Exercisementioning
confidence: 99%
“…Participation in scootering exercise has increased in popularity over the past two decades (Kijima et al, 2001(Kijima et al, , 2007 and may contribute to physical activity (PA) guidelines (e.g. 150-mins of moderate-intensity, 75-mins of vigorous-intensity or a combination thereof per week [O'Donovan et al, 2010;Departments of Health, 2011]), potentially improving cardiorespiratory fitness if scootering speeds (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…exercise intensity) provide sufficient physiological stimulus (e.g. >65% of heart rate maximum [HRmax]) (Pollock et al, 1998;Kijima et al, 2001Kijima et al, , 2007Arimoto et al, 2002). However, active transport is reportedly declining internationally in children (Tremblay et al, 2014;Ridley and Olds, 2016) and the prevalence of sedentary lifestyles and physical inactivity among adolescents and young adults is increasing (Rey-López et al, 2008;Hallal et al, 2012).…”
Section: Introductionmentioning
confidence: 99%